2005
DOI: 10.1274/jmor.22.178
|View full text |Cite
|
Sign up to set email alerts
|

Gel-Loading Tip Vitrification of In Vitro-Matured Bovine Oocytes and Subsequent Embryo Production by IVF and Nuclear Transfer

Abstract: T h e p u r p o s e o f t h i s s t u d y w a s t o cryopreserve bovine oocytes for subsequent blastocyst production by in vitro fertilization (IVF) and somatic cell nuclear transfer (SCNT). A vitrification procedure using g e l -l o a d i n g t i p s a s c o n t a i n e r s w a s a p p l i e d t ocryopreserve in vitro-matured and denuded oocytes. In Experiment 1, oocytes were vitrified-warmed in vitrification solution (VS) containing 25, 28, 31, or 40% e th y le ne gl ycol (EG) an d 1 . 0 M su crose . T he pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Vajta et al ( 1998 ) reported that a very high cooling rate (>20,000°C/min) can be achieved in an open pulled straw (OPS), resulting in a 13% blastocyst yield from post‐warmed bovine MII oocytes and a calf birth, followed by a few minor modifications as superfine OPS (Isachenko et al, 2001 ) and sealed pulled straw (Chen et al, 2001 ). Conventional disposable plastic tools were successfully used for the MVC vitrification of bovine oocytes, as reported with the gel‐loading tip (Tominaga et al, 2005 ) or flexipet‐denuding pipette (Morató et al, 2008 ). Because of the big market for human ART, a closed system using CryoTip® (Fujifilm Irvine Scientific) has been commercialized and is widespread in infertility clinics (Kuwayama, Vajta, Ieda, et al, 2005 ; VerMilyea & Brewer, 2017 ).…”
Section: Cryodevices For Oocyte Mvc Vitrificationmentioning
confidence: 99%
“…Vajta et al ( 1998 ) reported that a very high cooling rate (>20,000°C/min) can be achieved in an open pulled straw (OPS), resulting in a 13% blastocyst yield from post‐warmed bovine MII oocytes and a calf birth, followed by a few minor modifications as superfine OPS (Isachenko et al, 2001 ) and sealed pulled straw (Chen et al, 2001 ). Conventional disposable plastic tools were successfully used for the MVC vitrification of bovine oocytes, as reported with the gel‐loading tip (Tominaga et al, 2005 ) or flexipet‐denuding pipette (Morató et al, 2008 ). Because of the big market for human ART, a closed system using CryoTip® (Fujifilm Irvine Scientific) has been commercialized and is widespread in infertility clinics (Kuwayama, Vajta, Ieda, et al, 2005 ; VerMilyea & Brewer, 2017 ).…”
Section: Cryodevices For Oocyte Mvc Vitrificationmentioning
confidence: 99%
“…Nevertheless, the poor availability of bovine ovaries in our laboratory and a daily limit on the number of treated oocytes (less than 10) forced us to use the cryopreserved oocytes in the present study. The gel-loading tip vitrification procedure, characterized by an ultra-rapid cooling rate (Tominaga & Hamada, 2001), was found to be a promising method for cryopreservation of bovine oocytes after some modifications (Tominaga et al, 2005). However, an adverse effect of using vitrified oocytes and/or re-frozen spermatozoa on sperm aster formation cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…After maturation culture, oocytes were freed from cumulus cells by vortex-mixing and pipetting, and only oocytes which had extruded the first polar body were cryopreserved according to the method described by Tominaga et al (2005) with a few modifications. Briefly, groups of five oocytes were exposed to 3% (v/v) ethylene glycol (EG; Wako Pure Chemical Industries, Osaka, Japan) and 20% FBS in TCM199 for 12-15 min at 37 • C and then transferred to a vitrification solution composed of 31% EG, 1.0 M sucrose (Wako) and 20% FBS in TCM199 at the same temperature.…”
Section: Preparation Of Bovine Oocytesmentioning
confidence: 99%
See 1 more Smart Citation